Trabalenguas - Longo, Alejandra; Chaskielberg, Daniel (New York : Scholastic, 2004)
An illustrated collection of riddles and tongue twisters in Spanish.
"Scholastic en espanol"--Cover.
Text in Spanish.
Keywords: Riddles; Tongue twisters; Spanish language materials